Headache in Children and Adolescents A Case-Based Approach - Abu-Arafeh, Ishaq; Özge, Aynur (Springer International Publishing : Imprint: Springer, 2016)
This book assists appropriate headache assessment and decision-making in pediatrics. It covers many aspects and causes of headache disorders in children and adolescents using case studies to illustrate important points in history, examination, diagnosis, choice of management approach, therapy selection, and communication of the most helpful advice to the child and parents.   Case studies have been taken from real clinical practice and presented in a consistent style. They are discussed by the authors to highlight important points in history, important positive and negative points in examination, the diagnosis, and full analysis and justification of treatment options.     Headache in Children and Adolescents: A Case-Based Approach is an ideal reference for primary care physicians, paediatricians, neurologists and paediatric neurologists in their daily practice, in their consulting rooms and wards.